Investigation of silicon-based encapsulation for MEMS structures using epi-based processing - Oh, Yun Sheng. (2009)
This report presents a theoretical study, design and simulation of an on-chip epipoly (Si-based) encapsulation on for advanced microelectromechanical systems (MEMS) e.g. for capacitive accelerometers. Test structures were designed to assess the epipoly encapsulation and their layout was drawn using L-edit software to create masks necessary for subsequent fabrication. The usage of epi-poly encapsulation is important for microelectronic processing because it allows further integration with subsequent wafer level packaging which can be incorporated into the process flow of CMOS-MEMS devices. Research papers were studied to find out how the fabrication process of MEMS can cause failures in MEMS operation. Proposals were then discussed on the ways to improve the fabrication processes or the usage of alternative wafer level packaging to replace polysilicon encapsulation. This is essential because production costs may rise due to replacement of faulty MEMS with new ones.